One‐pot sequence‐selective synthesis of polylactone‐containing block terpolymers based on renewable terpenoid‐derived monomer and a simple organocatalyst. Issue 20 (21st July 2022) - Xie, Hongyan; Feng, Jiabing; Yang, Xiaoxia; Zhao, Yan; Song, Pingan; Wang, Hao; Xu, Zhiguang
Abstract: In this work, we report the synthesis and polymerization performances of terpenoid‐derived camphoric anhydride (CA). Utilizing simple organo‐base t BuP2 as the catalyst, CA can polymerize with various epoxides by efficient and controlled ring‐opening alternating copolymerization (ROAC) to afford perfectly alternating poly(CA‐ alt ‐epoxide). Kinetic study shows that the polymerization proceeds following zero‐order dependence on the concentration of CA. The self‐switchable terpolymerization from the mixture of CA, propylene oxide (PO) and ε ‐caprolactone (CL) is conducted under the catalysis of t BuP2 . First, ROAC of CA and PO is carried out exclusively with benzyl alcohol as initiator. Then, block copolymer (BCP) poly(CA‐ alt ‐PO)‐ b ‐PCL is obtained via the sequential polymerizations after the complete consumption of CA. The followed ring‐opening polymerization (ROP) of CL is initiated by the terminal hydroxyl of the ROAC‐resulted poly(CA‐ alt ‐PO) polyester without external stimulus. During the process, the excess PO compound remains intact. The one‐pot synthesis displays distinct living nature and perfect chemoselectivity. The as‐prepared terpenoid‐derived alternating and BCP's exhibit elevated thermal properties. Abstract :